Advancing Corporate Climate Accountability in Nigeria: Lessons from South Africa and the United Kingdom - Faga, Hemen Philip; Igwenagu, Uchenna Rodney (Lampung Journal of International Law, 2025)
The global climate crisis demands enforceable legal frameworks to hold high-emission corporations accountable. Nigeria, Africa’s largest economy and a major oil producer, remains hampered by fragmented laws, weak enforcement, and regulatory gaps. This paper compares Nigeria’s framework with South Africa’s carbon tax regime and the UK’s integration of climate risk into corporate governance, showing that effective accountability requires binding, economically significant obligations. Key deficiencies in Nigeria include oil and gas sector exemptions, non-justiciable environmental rights, the absence of a functional carbon tax, and discretionary corporate climate duties. Achieving national climate goals requires a shift from permissive regulation to strict, enforceable compliance.